Assessing students: Real-world analyses underpinned by economic theory - Caroline Elliott; Vudayagiri N. Balasubramanyam (Cogent Economics & Finance, 2016)
Having highlighted the importance of designing assessments for university economics students that link technical material with practical applications, the paper outlines three such assessments that have been successfully applied with postgraduate and third year undergraduate-level students. The assessments ask students to use their knowledge of economic theories and empirical analyses to propose and debate policy positions or to analyse the strategy decisions of real firms.
Keywords: 330; assessment; active learning; economic tools for teaching